Nyadran Sebagai Media Perekat Sosial: Studi Fungsi Budaya Ruwahan Di Desa Sukorejo, Klaten - Imani, Chusna Mufidah Nur (Javano Islamicus, 2026)
The Nyadran tradition, also known as Ruwahan (Sya'ban), is an annual event held before ramadhan in sukorejo village. This study aims to understand the symbolic meaning and role of Nyadran as a social link or adhesive in sukorejo village, Klaten. In this study, the researcher used a qualitative method with a literature approach, focusing on the process of cleaning graves and the kembul bujana (social cleansing). The research findings indicate that Nyadran has significant spiritual (birrul walidain) and social functions. Kembul bujana is an effective ritual in facilitating egalitarianism and solidarity and serves as a mechanism for social reconciliation, often held before ramadhan. Therefore, it can be concluded that the Nyadran tradition has proven to be a powerful means of connecting or bonding socially, contributing to maintaining community harmony, as well as driving the micro-economy and preserving ecological wisdom amidst the tide of modernization.